STRATEGI SENIMAN ALAT MUSIK SAPE' FERINANDUS LAH DALAM MEMPERTAHANKAN EKSISTENSI TERHADAP PERKEMBANGAN MUSIK DI KALIMANTAN BARAT - Meyliska Devi Andriani; Yudhistira Supriatna; Asfar Muniir (Universitas Tanjungpura, 2022)
The purpose of this thesis was to examine the strategies of Fery Sape' in maintaining his existence as an artist. The method used was a descriptive method in the form of a qualitative approach. The data source for this research was the resource person Fery Sape' and the data were the strategies to maintain his existence, the inhibiting and supporting factors of his existence, the efforts to overcome the obstacles in maintaining his existence based on the results of theinterviews, and the observations with the resource person. The results of this study indicated that there are four strategies Fery Sape' uses in maintaining his existence namely promotion and existence through social and broadcasting media, production and sales of Sape' musical instruments, cooperation with the government, and performance at cultural events. In addition, there are three supporting factors namely collaboration with other musicians,supports from the government and art studios. There are two inhibiting factors which are the lack offunds to work and the impact of Covid-19 pandemic. Furthermore, there are four efforts to overcome these obstacles namely fostering regeneration, involving the role of the government, being more active in creating and maintaining good relations between musicians and the community. Therefore, it can be concluded that the existence of Fery Sape' as an artist until now still persists in line with the strategies he implements.